The angiogenic properties of human adipose-derived stem cells (HASCs) are modulated by the High mobility group box protein 1 (HMGB1). (15th December 2017) - Biscetti, Federico; Gentileschi, Stefano; Bertucci, Flavio; Servillo, Maria; Arena, Vincenzo; Angelini, Flavia; Stigliano, Egidio; Bonanno, Giuseppina; Scambia, Giovanni; Sacchetti, Benedetto; Pierelli, Luca; Landolfi, Raffaele; et al.
Abstract: Peripheral arterial disease (PAD), is a major health problem. Many studies have been focused on the possibilities of treatment offered by vascular regeneration. Human adipose-derived stem cells (HASCs), multipotent CD34 + stem cells found in the stromal-vascular fraction of adipose tissues, which are capable to differentiate into multiple mesenchymal cell types. The High mobility group box 1 protein (HMGB1) is a nuclear protein involved in angiogenesis. The aim of the study was to define the role of HMGB1 in cell therapy with HASCs, in an animal model of PAD. We induced unilateral ischemia in mice and we treated them with HASCs, with the specific HMGB1-inihibitor BoxA, with HMGB1 protein, and with the specific VEGF inhibitor sFlt1, alternately or concurrently. We measured the blood flow recovery in all mice. Immunohistochemical and ELISA analyses was performed to evaluate the number of vessels and the VEGF tissue content. None auto-amputation occurred and there have been no rejection reactions to the administration of HASCs. Animals co-treated with HASCs and HMGB1 protein had an improved blood flow recovery, compared to HASCs-treated mice. The post-ischemic angiogenesis was reduced when the HMGB1 pathway was blocked or when the VEGF activity was inhibited, in mice co-treated with HASCs and HMGB1. In conclusion, the HASCs treatment can be used in a mouse model of PAD to induce post-ischemic angiogenesis, modulating angiogenesis by HMGB1. This effect is mediated by VEGF activity. Although further data are needed, these findings shed light on possible new cell treatments for patients with PAD.